The management of rheumatoid arthritis patients at Rural Siddha Hospital, Kodikamam, Jaffna, Sri Lanka - Miraaj, R.; Miraaj, V. (Conference Series, 2018)
The rheumatoid arthritis is a chronic, systemic inflammatory disorder that mainly attacks the joints. It also affects several tissues and organs such as lungs, pleura, pericardium, heart and sclera. This produces an inflammatory synovitis that often progresses to the destruction of the articular cartilage and ankylosis of the joints. About 1% of the world’s population is affected by rheumatoid arthritis. Woman are affected three times more often than men. Onset is most frequent between the ages of 40 and 50 but people of any age can be affected. In siddha medicine the same clinical symptoms are described under the Vali Azhal Keel Vayu. This is an observational case study and it was conducted at Rural Siddha Hospital, Kodikamam, Jaffna. The permission for this study is taken from the MOIC, Rural Siddha Hospital, Kodikamam, Jaffna. Patient consent was taken for this study in written from to take necessary photographs. One female rheumatoid arthritis patient was selected and she was treated three weeks in the ward. Siddha and ayurvedic drugs only were given internally and externally. Moreover the dietary regiments also were advised. Before and after the treatment the progresses of the disease was recorded as photograph and on BHT. The rheumatoid factor was 46 IU/L after the treatment while it was 185 IU/L before treatment. The pain and swelling of right knee joint were markedly decreased after the treatment and the degree of swelling and pain were estimated in certain conditions. Therefore, according to this clinical observation, we can recommend this treatment method as an efficient for management of rheumatoid arthritis patients.